Mobilização para além das fronteiras: semelhanças transnacionais dos movimentos sociais de origem virtual pelo mundo - Luciana de Oliveira Leal Halbritter; Maria Inácia D\u2019Ávila Neto (Ciências Sociais Unisinos)
In June 2013, the social movement started in São Paulo took the streets with public demonstrations in several cities across the country. What began as revolt due to the increase in public transportation fares led to the rejection of constitutional draft amendments, voting bills, and promises of changes in critical sectors such as health and education. Millions of people have joined the movement through social networks, promoting the events, defending ideas, calling friends to join and participate. These movements are not a Brazilian originality, as they repeat similar movements in other countries. All of them have similar dynamics, using the Internet, especially social networks like Facebook, to spread the mobilization and to invite more people to participate, despite the inherent differences of their claims. If, on the one hand, globalization serves to expand and strengthen contemporary capitalism, on the other, it makes popular mobilization possible globally. There is the emergence of a transnational political representation. Given this context, the main objective of this study is to analyze how the relationships between citizens were established in virtual networks and extrapolated the virtual realm so as to interfere directly in the real world. Methodologically, it analyzes news reports of the time of the mobilizations as well as the reactions and responses from the powers that be compared to what occurred in other countries with movements similar in their dynamics, drawing a parallel between them. On the basis of this analysis, it proposes hypotheses to explain the phenomenon and points to possible developments in theories of social movements.